The effect of dietary fiber on insulin resistance in obesity: A literature review - Santri Dwizamzami Faridahanum; Fariz Nurwidya; Yohannessa Wulandari (World Nutrition Journal, 2021)
Introduction Obesity has become a significant public health problem in developing countries such as Indonesia. According to WHO, 13% of adults aged 18 years and over were obese in 2016. In Indonesia, 21.8% of adults were obese. In obesity, the body's resistance to insulin will develop. Some studies showed a probable link between dietary fiber and insulin resistance. This research aims to investigate the role of the dietary fiber on insulin resistance in obesity. Methods: This study is a literature study to determine the effect of dietary fiber on insulin resistance in obesity with sources from scientific publications 10 years back. The databases were PubMed and Google Scholar. The search term used was using the explode function for subgroup terms with operators (â€œand,â€ or) for â€œdietary fiberâ€, â€œobesityâ€, â€œinsulin resistanceâ€. Hand-searching was used to identify further potential eligible studies. There were no language restrictions, however only publications with full texts available were included. Total 138 publications titles and abstract were screened for their relevance to this literature review. Results: A total of 25 publications were finally included. There are cross-sectional studies, randomized clinical trial, cohort studies, and article review. Some studies showed that dietary fiber had an effect on improve insulin resistance, but other studies did not find this effect. Conclusion: The studies of dietary fiber effect on insulin resistance have inconsistent results. In the future, further studies are required for better understanding about the effect of dietary fiber on insulin resistance in obesity